Teacher’s Technological Pedagogical Content Knowledge in Developing Learning Materials - Ella Wulandari (Universitas Negeri Yogyakarta, 2019)
The provision of appropriate learning materials is essential in curriculum enactment as the prescribed competences and learning method are usually advised in textbooks supplied to support its implementation. However, government-supplied textbook cannot always address schools’ and students’ different needs. Teachers are, therefore, required to have the skills to develop their own learning materials to meet curriculum. In Indonesia, higher order thinking skills (HOTS) and technology are required to be integrated in the teaching and learning activities of all subjects including English. It is, then, important to survey teacher’s knowledge in materials development to help them acquire the required skills in developing materials in line with curriculum. This paper presents a survey study on junior secondary school teachers in Yogyakarta about their technological pedagogical content knowledge. A questionnaire was administered followed by an interview with selected teachers for further elaboration. The instrument was adapted from Schmidt et al (2009) and aimed to reveal teacher’s knowledge on teaching and technology and how they apply this knowledge into materials development processes. The finding suggests aspects of teacher’s knowledge that need further training and possible effective methods for their training as well as professional development design.Keywords: curriculum, materials development, teacher’s knowledge